The novel "The Glass Bead Game" by Hermann Hesse and postmodernism - Arakelyan, Ara (Bulletin of Yerevan University B: Philology, 2022)
The article deals with the problems related to the connections of the novel "The Glass Bead Game" by Hermann Hesse and postmodernism. The article touches upon the history of postmodernism, the last most influential manifestation of Western aesthetic-theoretical thought, which also can contain paradoxes. One of them is that, although aesthetes and philosophers have been talking about postmodernism for seven decades, there is still no consensus about this literary trend. There are certain deas (chaos, eclecticism, simulacrum, multiculturalism, game, etc.) that are actually points of contact between Hesse's novel and postmodernism.  At the same time, the important fact is emphasized that Hermann Hesse's novel, published decades before the stormy debates of postmodernists, contributes to a certain extent to the dissemination of these ideas among postmodern aestheticians.
Keywords: modernism; postmodernism; chaos; literary eclecticism; multiculturalism; game; destruction; text